Performance-Based Adaptive Automation: Number of Task Types and Response Time Measures Triggering Level of Automation Changes. (September 2021) - Calhoun, Gloria; Ruff, Heath; Frost, Elizabeth; Bowman, Sarah; Bartik, Jessica; Behymer, Kyle
A key challenge facing automation designers is how to achieve an ideal balance of system automation with human interaction for optimal operator decision making and system performance. A performance-based adaptive automation algorithm was evaluated with two versus six monitored task types. Results illustrate the importance of level of automation choices in control schemes.